Sengketa Harta Bersama Pasca Perceraian Ditinjau dari Hukum Perdata Barat - Amanda Lauza Putri (Dinasti Review Publisher, 2024)
Everyone hopes to have a happy and stable family in marriage, although in reality, not everyone can achieve it. Often, conflicts in marital relationships lead to the end of the marriage through divorce, which is frequently followed by joint property lawsuits, as seen in Decision Number 71/PDT.G/2020/PN SO. Mrs. F and Mr. Y married on July 7, 2007, in Surabaya and officially divorced, recorded at the Civil Registry Office in Sorong on August 28, 2020. The disputed joint property in this lawsuit includes one plot of land and the income from their jointly owned shop from November 2019 to September 2020. In October 2020, Mrs. F filed a joint property lawsuit at the Sorong District Court, which was then approved by the Panel of Judges, dividing the ownership of the joint property equally. Both items are considered joint property of the former married couple because they were acquired during their marriage. To avoid conflicts over joint property after a divorce, the former spouses should promptly create a Joint Property Division Deed before a Notary. For this writing, the author uses a normative juridical method, where the law is explained as anything contained in legislation or rules that are deemed appropriate and used as guidelines for human behavior.